Effect of sodium hexametaphosphate on the flotation separation of biotite and K-feldspar in the NaOL/DDA system - Xingyu Hu; Bo Mei; Lingfeng Shen; Wei Sun; Yanxiu Wang; Jinghua Huang; Li Wang (Minerals Engineering, 2026)

Wearable triboelectric sensor based on a single-line-contact electrode architecture for gesture recognition and human–machine interaction - Long Li; Jingyun Dai; Jiayang Lyu; Yifan Shen; Yanmin Guo; Lingfeng Du; Zhiqian Wei; Xiongtu Zhou; Yongai Zhang; Hyung-Soon Kim; Dianlun Li; Kun Wang; et al. (Chemical Engineering Journal, 2026)

Biphasic multiplex PCR based on bead array for high-throughput and sensitive authentication of meat products - Lingfeng Yan; Rong Cao; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Food Control, 2026)

Reverse flotation desilication of bauxite Ore: unraveling the mechanism of Cu(II)-SDSo in selective separation of kaolinite from diaspore - Boai Zhang; Lingfeng Shen; Honghu Tang; Jianjun Wang; Wei Sun; Jianyong He; Li Wang (Minerals Engineering, 2026)

Strongly coordinating anions and cosolvent synergy enabled lithium metal batteries - Yutao Liu; Yi Li; LingFeng Zhang; Mengmeng Tan; QiXian Zhang; Wei Lü (Chemical Engineering Journal, 2026)

Integrative multi-omics identifies CYP1B1 as a candidate molecular link between toxicant exposure and ferroptosis-related epithelial stress in COPD - Lingfeng Liu; Mingjun Jiang; Muzi Lei; Kun Du; Xiangyang Ye; Dafei Wei; Xiaowu Tan; Zhuang Mi; Yao Tang; Ruiting Sun; Sha Liu (Inflammation Research, 2026)

Nanoplastic exposure induces exoskeletal misdevelopment in juvenile Tachypleus tridentatus: Compensatory hardening versus molecular suppression - Lingfeng Jiang; Youji Wang; James Kar-Hei Fang; Khor Waiho; Wei Liu; Jae-Seong Lee; Xiaowan Ma; Menghong Hu (Marine Pollution Bulletin, 2026)

Target of contracted management rights, value orientations, and management behaviors of forest farmers in China - Fengxia Chen; Yan Xu; Yitong Yang; Lingfeng Wei (Journal of Rural Studies, 2026)

Development of a high-throughput sensitive SB-PCR assay for rapid detection of laboratory-escaped antibiotic resistance genes - Lingfeng Yan; Shengnan Liu; Rong Cao; Azadeh Nilghaz; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Journal of Environmental Chemical Engineering, 2026)

Enhancement mechanism of metal ions on lepidolite flotation in mixed NaOL/DDA system - Rui Xu; Lingfeng Shen; Jinghua Huang; Honghu Tang; Haisheng Han; Wei Sun; Li Wang (Minerals Engineering, 2025)

The Ran GTPase inhibits SGIV and RGNNV infection by upregulating host immune response in grouper - Xiaozhi Wen; Lingfeng Guan; Liqun Wang; Zihan Zhang; Xinyan Wei; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2025)

Adaptive Responses in Byssal Growth and Shedding: Insights from Pteria penguin Under Thread Trimming and Non-Trimming Conditions - Hebert Ely Vasquez; Shangkun Wei; Guoliang Yang; Lingfeng Wang; Peixuan Yu; Mingyue Dong; Chao Yuan; Xing Zheng (Journal of Marine Science and Engineering, 2025)
Bivalves use byssal threads for attachment and locomotion, periodically shedding and regenerating them. In the winged pearl oyster Pteria penguin—known for its strong byssus and its role in the pearl industry—shedding may occur when the byssal stalk reaches a critical size, although the underlying mechanism remains unclear. This study investigated whether artificial manipulation of the byssus (via trimming) could stimulate thread production and promote shedding in adult P. penguin from two size groups. Byssal threads attached to the substrate were trimmed every 3–5 days over a 30-day period and compared to untrimmed controls. Oysters with trimmed byssus produced significantly more threads, with smaller individuals outperforming larger ones in both thread count and byssal stalk diameter. Moreover, small oysters exhibited a higher frequency of complete byssal shedding. These findings suggest that trimming stimulates thread production and accelerates stalk thickening, potentially triggering shedding due to spatial constraints at the attachment site. This response appears to reflect an adaptive mechanism for maintaining effective attachment and may help explain how mechanical or environmental cues influence byssal dynamics. Understanding this process offers new insight into the behavioral and physiological plasticity of P. penguin, with potential applications in pearl oyster management and aquaculture.

Advanced design of the crushing chamber for the sugarcane top silage cutter in harvester with experiments and simulation - Peng Huo; Shaochun Ma; Jun Qian; Weiqing Li; Baocheng Zhou; Wei Liu; Wenpeng Liang; Wenzhi Li; Changyu Wang; Sha Yang; Lingfeng Li; Yechen Li; et al. (Computers and Electronics in Agriculture, 2025)

Survival and physiological responses of pearl oyster Pinctada maxima seedlings: Comparative analysis of wet (submerged) and dry (waterless) transportation methods - Xing Zheng; Ze Yin; Lingfeng Wang; Shangkun Wei; Meng Zhang; Xinfei Shao; Hebert Ely Vasquez; Zhifeng Gu (Aquaculture, 2025)

Mapping critical soil moisture thresholds of water stress for global grasslands - Lingfeng Shi; Yanlian Zhou; Wei He; Zhoutong Dong; Zhuoyou Jiang; Yuyan Wang; Yibo Liu; Weimin Ju; Zheng Duan (Journal of Hydrology, 2024)

High pre-tension reinforcing technology and design for ultra-shallow buried large-span urban tunnels - Qi Wang; Huayong Wei; Bei Jiang; Xuepeng Wang; Lingfeng Sun; Manchao He (International Journal of Rock Mechanics and Mining Sciences, 2024)

Influence of corrosion on seismic performance of steel beam-to-column connections - Yuelin Zhang; Cheng Fang; Wei Wang; Lingfeng Wu; Peng Cao (Engineering Structures, 2024)

EEG-FRM: a neural network based familiar and unfamiliar face EEG recognition method - Chao Chen; Lingfeng Fan; Ying Gao; Shuang Qiu; Wei Wei; Huiguang He (Cognitive Neurodynamics, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Differentiation of fungal trophic guilds to long-term nitrogen addition in a poplar plantation - Nan Yang; Jiangbao Zhang; Jiani Hua; Baohan Song; Tianyi Wang; Wei Xing; Guobing Wang; Lingfeng Mao; Honghua Ruan (Forest Ecology and Management, 2024)

Stable oganocopper(III) complexes generated via oxidative addition - Lingfeng Yin; Wei Liu (Science Bulletin, 2024)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Molecular-level insights into the heterogeneous variations and dynamic formation mechanism of leached dissolved organic matter during the photoaging of polystyrene microplastics - Fanhao Song; Tingting Li; Jin Hur; Quan Shi; Fengchang Wu; Wei He; Di Shi; Chen He; Lingfeng Zhou; Mingqi Ruan; Yuhan Cao (Water Research, 2023)

Solvent effect to modulate nitrogen dopant in Co-N-C catalysts for oxygen reduction reaction acceleration - Lingfeng Li; Guokang Han; Yandi Wen; Yuxin Liu; Rang Xiao; Wei Zhang; Fanpeng Kong; Lei Du; Yulin Ma; Pengjian Zuo; Chunyu Du; Geping Yin (Fuel, 2023)

Fabrication of immobilized lipases for efficient preparation of 1,3-dioleoyl-2-palmitoylglycerol - Lihong He; Can Zeng; Lingfeng Wei; Li Xu; Fenglin Song; Jianrong Huang; Nanjing Zhong (Food Chemistry, 2023)

Spatio-temporal heterogeneity in the international trade resilience during COVID-19 - Wei Luo; Lingfeng He; Zihui Yang; Shirui Zhang; Yong Wang; Dianbo Liu; Sheng Hu; Li He; Jizhe Xia; Min Chen (Applied Geography, 2023)

Halide-chalcogenide hetero-structure for efficient and stable perovskite solar cells - Riming Nie; Zeliang Wei; Aarti Mehta; Lingfeng Chao; Jiaxing Gao; Weicun Chu; Zhongping Li; Han Miao; Yonghua Chen; Wanlin Guo (Chemical Engineering Journal, 2023)

The effects of natural weathering ages on mineralogical, physical, and chemical properties of stacking molybdenum tailings - Li Wang; Lingfeng Shen; Wei Sun; Bin Ji; Honghu Tang (Environmental Science and Pollution Research, 2022)

Three-Dimensional Fluid–Solid Coupling Numerical Simulation of Effects of Underlying Karst Cave on Shield Tunnel Through Sand Stratum - Wei Wang; Shiming Gao; Youwei Min; Lingfeng Liu; Jianping Chen (Geotechnical and Geological Engineering, 2019)